Price Discrimination in the European Clothing Sector - Gianpaolo Rossini (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1988)
Price differences for identical goods across EEC countries have been for some years a sign of lagging integration.
Keywords: 330